The relevance of the national political parties in the context of local party leadership in the Fifth Congressional District of Leyte, 1992-1995 - Pando, Francisco S. (1997)
This study is an attempt to explain the relevance of the national political parties in the context of local party leadership in the Fifth Congressional District of Leyte between 1992 and 1995. It looks on two elements in accomplishing the task, and these are the local party activities. The first element intends to determine the local leaders' relation to the party by examining the aspects of motivation, grasp of ideology, responsibility, loyalty and status. While the second element identifies the political parties' contribution or support to local party activities. This involves the concrete party support such as the financial, organizational, ideological, legal, security, special projects, and others. It also determines the extent of the support in terms of sufficiency of each of the items categorized.